3(r+1)-2(3-2r)-3(3-r)=2(r+5)-4

Simple and best practice solution for 3(r+1)-2(3-2r)-3(3-r)=2(r+5)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(r+1)-2(3-2r)-3(3-r)=2(r+5)-4 equation:


Simplifying
3(r + 1) + -2(3 + -2r) + -3(3 + -1r) = 2(r + 5) + -4

Reorder the terms:
3(1 + r) + -2(3 + -2r) + -3(3 + -1r) = 2(r + 5) + -4
(1 * 3 + r * 3) + -2(3 + -2r) + -3(3 + -1r) = 2(r + 5) + -4
(3 + 3r) + -2(3 + -2r) + -3(3 + -1r) = 2(r + 5) + -4
3 + 3r + (3 * -2 + -2r * -2) + -3(3 + -1r) = 2(r + 5) + -4
3 + 3r + (-6 + 4r) + -3(3 + -1r) = 2(r + 5) + -4
3 + 3r + -6 + 4r + (3 * -3 + -1r * -3) = 2(r + 5) + -4
3 + 3r + -6 + 4r + (-9 + 3r) = 2(r + 5) + -4

Reorder the terms:
3 + -6 + -9 + 3r + 4r + 3r = 2(r + 5) + -4

Combine like terms: 3 + -6 = -3
-3 + -9 + 3r + 4r + 3r = 2(r + 5) + -4

Combine like terms: -3 + -9 = -12
-12 + 3r + 4r + 3r = 2(r + 5) + -4

Combine like terms: 3r + 4r = 7r
-12 + 7r + 3r = 2(r + 5) + -4

Combine like terms: 7r + 3r = 10r
-12 + 10r = 2(r + 5) + -4

Reorder the terms:
-12 + 10r = 2(5 + r) + -4
-12 + 10r = (5 * 2 + r * 2) + -4
-12 + 10r = (10 + 2r) + -4

Reorder the terms:
-12 + 10r = 10 + -4 + 2r

Combine like terms: 10 + -4 = 6
-12 + 10r = 6 + 2r

Solving
-12 + 10r = 6 + 2r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-2r' to each side of the equation.
-12 + 10r + -2r = 6 + 2r + -2r

Combine like terms: 10r + -2r = 8r
-12 + 8r = 6 + 2r + -2r

Combine like terms: 2r + -2r = 0
-12 + 8r = 6 + 0
-12 + 8r = 6

Add '12' to each side of the equation.
-12 + 12 + 8r = 6 + 12

Combine like terms: -12 + 12 = 0
0 + 8r = 6 + 12
8r = 6 + 12

Combine like terms: 6 + 12 = 18
8r = 18

Divide each side by '8'.
r = 2.25

Simplifying
r = 2.25

See similar equations:

| =60ln(x+1) | | (3+2i)-(5-7i)=0 | | 35n-4=66 | | 3w^2=-27w | | 8X+30=10X | | -5(z-9)(-z-3)=0 | | 5z+16=4z-10 | | 2X-30-X=30-4X | | -4z(z-3)(z-9)=0 | | 15x-52=5x+18 | | x^2+10x-73= | | x^2+10x-73= | | 10X=9+4X+51 | | x^2+10x-73=0 | | (y-4)(y+8)=0 | | x^2+6x-73=0 | | 17x-(6x-4)=48 | | 2(x-18)=-2 | | -4x+66=3x+38 | | 4+3*2=14 | | 3x-10+5x+10=180 | | -3y-3=2-2y | | x+x^2=25.862 | | y+1x+0=2 | | 7x+11=3x+79 | | -6v-6(2x-4)=84 | | 7*x^2-11-30=0 | | 2x^3-9x^2-1=0 | | 7d-r(d+8)=-8 | | 24x^2-26x-28= | | 3sin(2x)=-2 | | 2+A+33=12 |

Equations solver categories